The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/micr.30058
|View full text |Cite
|
Sign up to set email alerts
|

Remote ischemic perconditioning attenuates acute inflammation of experimental musculocutaneous flaps following ischemia‐reperfusion injury

Abstract: RIPER reduced IL-6 and IL-12p40 secretion during reperfusion of porcine musculocutaneous flaps, when compared with hypothermic ischemic flaps and normothermic ischemic flaps without RIPER. © 2016 Wiley Periodicals, Inc. Microsurgery 37:148-155, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…Four hours of ischemia was chosen to induce substantial flap ischemia–reperfusion injury without exceeding the critical ischemia time of musculocutaneous flaps and thereby risking microcirculatory failure. Our previous study confirmed that the flaps were exposed to ischemia–reperfusion injury shown by histological and immunological analyses (Krag et al, ). We administered RIC after onset of flap ischemia and before reperfusion, so‐called remote ischemic perconditioning (Schmidt et al, ) to study an isolated effect on coagulation after flap ischemia–reperfusion injury and to avoid a perconditioning effect on the flaps.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Four hours of ischemia was chosen to induce substantial flap ischemia–reperfusion injury without exceeding the critical ischemia time of musculocutaneous flaps and thereby risking microcirculatory failure. Our previous study confirmed that the flaps were exposed to ischemia–reperfusion injury shown by histological and immunological analyses (Krag et al, ). We administered RIC after onset of flap ischemia and before reperfusion, so‐called remote ischemic perconditioning (Schmidt et al, ) to study an isolated effect on coagulation after flap ischemia–reperfusion injury and to avoid a perconditioning effect on the flaps.…”
Section: Discussionsupporting
confidence: 85%
“…The systemic coagulation marker response to flap ischemia–reperfusion injury was investigated by comparing measurements obtained before flap reperfusion with 5 h of reperfusion, because flap inflammation peaked at 5 h of reperfusion in the same model (Krag et al, ). Musculocutaneous flap ischemia–reperfusion injury reduced thrombin generation lag time and time‐to‐peak thrombin indicating hypercoagulation, but it also reduced peak thrombin and ETP indicating hypocoagulation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations